The Protection of The Law Patients Privacy of Health Services - Johanes Deo Fau; Yustina Sila (Faculty of Law, Merdeka University Surabaya, Indonesia, 2020)
This research read:“ The protection of the law patients privacy Of health services with 2 (two) case formulations, are: (1) How the regulation of the protection of the law privacy a patient in health services?; (2) How was the end of law a violation of privacy for patients of health workers?. The research is the kind of research law with uses the method law normative. In addition, the study also used the conceptual kinds of abilities. the statute and approach. This research result indicates that privacy is the right of patients that have to be fulfilled by health workers and the means of health services and shall constitutes the obligation of health workers to keep privacy patients who it serves in the act of health, the act of health workers, the act of practices medicine, the act of nursing, regulations related minister midwife practice that requires health workers behind the secrecy was related to the record good patients medical and privacy. A breach of privacy by health workers towards patients will cause due to law when patients and their families feel aggrieved. Due to administrative law civil and criminal can be used as material. accusation of health workers. Hence it is expected that the act of explicitly able to regulate precisely because given health workers keep privacy patients and clarify about privacy rights inherent in themselves patients who must be protected and be protected conducting socialization on the importance of maintaining privacy patients called on the government as well as a means of health services to facilitate a patient to complained about services received that may violate the right of privacy she would had to thrash out as soon as possible in the process of mediation in order to avoid a process litigation can force own. financial losses for.